Odpowiedzi

2010-02-28T14:42:02+01:00
A) 2(x+3)-5>-2x-7
2x+6-5 > -2x -7
2x+2x > -7-6+5
4x > -8
x < -2

b) -2(x-1)+5x>7x+12
-2x+2 +5x > 7x+12
-2x+5x-7x > 12-2
-4x > 10
x < - 2 i 2/4


d) 0,7x-2≤0,9x-0,1
0,7x - 0,9x ≤ 2-0,1
-0,2 x ≤ 1,9
x ≥ -9,5

e) -x+3≥-(3x-2)
-x+3 ≥ -3x +2
-x+3x ≥ 2-3
2x ≥-1
x ≤ - 1/2

f) 0,1(2x-3)<-0,6x+1
0,2x-0,3 < -0,6x + 1
0,2x +0,6x < 1 +0,3
0,8x <1,3
x > 1,625
2010-02-28T14:47:09+01:00
A) 2(x+3)-5>-2x-7
2x+6-5 > -2x-7
2x+2x >-7-6+5
4x > -8 / :4
x > -2
rozwiązaniem jest zbiór (-2 ; +∞)

b) -2(x-1)+5x>7x+12
-2x+2+5x > 7x+12
-2x+5x-7x > 12-2
-4x > 10 / : (-4)
x < -¹⁰/₄
x < -2½
rozwiązaniem jest zbiór (-∞ ; -2½)

c) ⅓x+1>-x+2
⅓x+x > 2-1
1⅓x > 1
⁴/₃ x > 1 / * ¾
x > ¾
rozwiązaniem jest zbiór ( ¾ ; +∞)

d) 0,7x-2≤0,9x-0,1
0,7x-0,9x ≤ -0,1+2
-0,2x ≤ 1,9 / : (-0,2)
x ≥ -9,5
rozwiązaniem jest zbiór <-9,5 ; +∞)

e) -x+3≥-(3x-2)
-x+3 ≥ -3x+2
-x+3x ≥ 2-3
2x ≥ -1 / :2
x ≥ - ½
rozwiązaniem jest zbiór <- ½; +∞)

f) 0,1(2x-3)<-0,6x+1
0,2x-0,3 < -0,6x+1
0,2x+0,6x < 1+0,3
0,8x < 1,3 / : 0,8
x < 1,625
rozwiązaniem jest zbiór (-∞ ; 1,625
2010-02-28T14:49:09+01:00
A)
2(x+3)-5>-2x-7
2x+6-5>-2x-7
2x+1>-2x-7
2x+2x>-7-1
4x>-8 /÷4
x>-2

b)
-2(x-1)+5x>7x+12
-2x+2+5x>7x+12
-2x+5x-7x>12-2
-4x>10 /÷(-4)
x<2½

c)
⅓x+1>-x+2
⅓x+x>2-1
1⅓x>1
4/3x>1 /*¾
x>¾
x>0,75

d)
0,7x-2≤0,9x-0,1
0,7x-0,9x≤-0,1+2
-0,2x≤1,9
-⅕x≤1,9 /*(-5)
x≥-9,5

e)
-x+3≥-(3x-2)
-x+3≥-3x+2
-x+3x≥2-3
2x≥-1 /÷2
x≥-½

f)
0,1(2x-3)<-0,6x+1
0,2x-0,3<-0,6x+1
0,2x+0,6x<1+0,3
0,8x<1,3 /÷0,8
x<1,625